2012
DOI: 10.1002/wsb.214
|View full text |Cite
|
Sign up to set email alerts
|

Artificial roosts for tree‐roosting bats in northern Arizona

Abstract: Bats use large (69 cm mean diameter) ponderosa pine (Pinus ponderosa) snags for maternity roosts in northern Arizona. Anthropogenic causes have altered forest structure, decreasing density of large snags. To examine use of artificial roosts for bats in these forests, we selected 26 sites and 2 treatments (clustered, single) using 1 type of roost (resin or wood) per site. At each site, we installed 4 roosts on ponderosa pine trees with a cluster of 3 roosts (south-, east-, or west-facing; <20 m apart) and a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Boxes varied in dimensions, entrance locations, number of compartments, and thickness of wood. Several other types of roosts were designed to mimic exfoliating bark such as cedar shingles (singles and strings) strung around trees, tarpaper and plastic plus tarpaper (Whitaker et al ), and resin (Siders , Chambers et al , Mering and Chambers , Wilhelm ). The remaining roosts were constructed to mimic other natural roost sites such as foliage, hollow trees, or caves.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Boxes varied in dimensions, entrance locations, number of compartments, and thickness of wood. Several other types of roosts were designed to mimic exfoliating bark such as cedar shingles (singles and strings) strung around trees, tarpaper and plastic plus tarpaper (Whitaker et al ), and resin (Siders , Chambers et al , Mering and Chambers , Wilhelm ). The remaining roosts were constructed to mimic other natural roost sites such as foliage, hollow trees, or caves.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies provided roosts facing different directions, but placed only one roost per tree. Mering and Chambers () found that east‐ and south‐facing roosts were used more and had warmer average temperatures than west‐facing roosts. Flaquer et al () had higher occupancy in east‐facing compared with west‐facing roosts on buildings.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations